Investigating the Effects of Intraprofessional Learning in Nursing Education: Protocol for a Longitudinal Study - Debra Kiegaldie; Ishanka Weerasekara; Louise Shaw (MDPI AG, 2023)
Interprofessional learning (IPL), where nursing students learn how to work with multiple health professionals in their future practice to deliver the highest quality of care, has become an essential feature of undergraduate nursing programs. Intraprofessional learning (IaPL) is where individuals of two or more disciplines within the same profession collaborate; however, there is a dearth of literature investigating its effects in nursing education. The aim of this study is to investigate the impact of IaPL on the development of nursing students' knowledge, skills, and attitudes for collaborative practice. The study will utilize a mixed methods approach with surveys conducted at six time points across two years of two nursing programs and focus groups at the end of the program. Participants will be recruited from the Diploma and Bachelor of Nursing programs at an Australian Training and Further Education institute. Four specific IaPL educational experiences incorporating simulation will be developed on aged care, mental health, complex care and acute care. The study will provide nursing students with multiple opportunities to develop the necessary capabilities for collaborative practice. It will longitudinally evaluate nursing students' attitudes towards IaPL and examine whether IaPL motivates Diploma of Nursing students to pathway into a Bachelor of Nursing degree. The study will also investigate awareness amongst nursing students of the scope of practice, roles and responsibilities of the nursing team.